2017
DOI: 10.1007/s40089-017-0220-4
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of palladium nanoparticles with leaf extract of Chrysophyllum cainito (Star apple) and their applications as efficient catalyst for C–C coupling and reduction reactions

Abstract: A simple green chemical method for the onestep synthesis of palladium nanoparticles (PdNPs) has been described by reducing palladium (II) chloride with the leaf extract of Chrysophyllum cainito in aqueous medium. The synthesis of the palladium nanoparticles completed within 2-3 h at room temperature, whereas on heat treatment (70-80°C), the synthesis of colloidal PdNPs completed almost instantly. The stabilized PdNPs have been characterized in detail by spectroscopic, electron microscopic and light scattering … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…Phytochemical extracts from Pimpinella tirupatiensis and Chrysophyllum caimito , which are rich in polyphenols, were used to synthesize PdNPs. 95,100 The resulting PdNPs were in the range of 12 to 170 nm with an absorbance value of 260 nm. Interestingly, a recent study identified that the size of PdNPs could be reduced by 2.85-fold when the concentration of plant extract was increased by 2-fold.…”
Section: Plant Extract Mediated Synthesismentioning
confidence: 99%
“…Phytochemical extracts from Pimpinella tirupatiensis and Chrysophyllum caimito , which are rich in polyphenols, were used to synthesize PdNPs. 95,100 The resulting PdNPs were in the range of 12 to 170 nm with an absorbance value of 260 nm. Interestingly, a recent study identified that the size of PdNPs could be reduced by 2.85-fold when the concentration of plant extract was increased by 2-fold.…”
Section: Plant Extract Mediated Synthesismentioning
confidence: 99%
“…Additional advantage of this method is that the extract itself acts as a stabilizer and no additional stabilizers are required. The extracts of Aspergillus fischeri [ 19 ], Epicoccum nigrum [ 20 ], bark of Mimusops elengi [ 21 ], leaf of Chrysophyllum cainito (Star apple) [ 22 ], bark of Abroma augusta Linn, [ 23 ] Backhousia citriodora [ 24 ], Breynia rhamnoides [ 25 ], Piper betle [ 26 ], pear extract [ 27 ] etc. have been utilized for the synthesis of AuNPs.…”
Section: Introductionmentioning
confidence: 99%
“…The bio-based nanospheres [39] consumed 40 min for the complete reduction of NiP, but the present investigation consumed 11 min only. In 2017, Majumdar et al [40] reported the Pd nanoparticle-mediated catalytic reduction NiP and the k app value was reported as 3.83 × 10 −3 s −1 . Hence, when compared with the literature, the present investigation yielded better results.…”
Section: Resultsmentioning
confidence: 99%